2014
DOI: 10.5901/mjss.2014.v5n6p453
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Sustainable Energy in sub-Saharan Africa and Possible Solutions

Abstract: This paper examines the problems of promoting sustainable energy in sub-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The lowest costs per kWh are obtained using WT 1 , while the 2 nd and 3 rd third positions in rank are taken, respectively by WT 3 and WT 2 . WT4 and WT 5 exhibit the same performance. WT 6 shows the highest cost per kWh of energy produced.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The lowest costs per kWh are obtained using WT 1 , while the 2 nd and 3 rd third positions in rank are taken, respectively by WT 3 and WT 2 . WT4 and WT 5 exhibit the same performance. WT 6 shows the highest cost per kWh of energy produced.…”
mentioning
confidence: 83%
“…Despite being the least growing region in terms of WE generation capacity, Africa has WE resources and potential that can meet its current needs, if properly tapped. Several studies have shown that the wind resource in Africa is greatest around the coasts and in the eastern highlands [4] [5]. However, the WE development in the African continent remains very slow as a result of limited support at the level of the continent, since the vast majority of WE projects necessitate financial support from organizations based out of the continent [6].…”
Section: Introductionmentioning
confidence: 99%
“…Expanding access to modern energy services had been an enormous challenge for developing countries, especially in the poorest countries (Legros et al, 2009). Part of the challenge to expanding energy access in SSA as argued by Ganda and Ngwakwe (2014) is the continued employment of fossil fuel subsidies and high transaction costs. Other associated problems include presence of monopoly structures in the energy sectors, large capital required to fund sustainable schemes, regulatory and macroeconomic risks in sustainable energy schemes, low carbon risk and negative social impacts.…”
Section: Brief Literature Overviewmentioning
confidence: 99%
“…Among causes of environmental issues, it is furtherly clear that our energy consumption has a detrimental impact on the environment and our health (Xing et al 2019). Sub Saharan Africa is certainly the most contrasted continent with a very dichotomy of energy systems (Ganda and Ngwakwe 2014). Inefficient traditional forms of energy, mainly fuelwood and charcoal, continue to dominate in most countries of sub-Saharan Africa, especially for cooking uses (Manfred Hafner, Simone Tagliapietra, and Lucia De Strasser 2018).…”
Section: Introductionmentioning
confidence: 99%